The development of interactive educational games to improve character values in early childhood - Rakimahwati, Rakimahwati; Fitri, Ramadaniah (International Journal of Research in Counseling and Education, 2021)
Based on the preliminary study that the researcher did, the researcher saw that there were still many children's character values that were not good, such as the difficulty of queuing and social interaction while in the school environment.This study aims to produce educational games to improve the valuesof early childhood characters that are valid, practical, and effective. This study uses the Sugiyono model development method (potential and problems, data collection, product design, design validation, usage trials, product revisions, product trials, design revisions, product revisions and mass production). The resulting development products consist of 2 types, namely manuals on the use of educational games to increase character values and educational game software to improve character values for early childhood. In the initial development process, the developer consults with media experts to get input and suggestions about the developed media. To determine the validity of the product, expert validation tests of media experts, material expert validation and field expert validation tests (expert lecturers) were carried out. The instrument of this research is a questionnaire which is used to determine the validity of the product. The results of the assessment were analyzed using a descriptive percentage analysis technique. Informants in this study were teachers and children. Data collection techniques used consisted of questionnaires, and documentation. The data analysis technique uses validity analysis, practicality analysis and effectiveness analysis.